2022
DOI: 10.1021/acsaem.2c00688
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the Impact of Fast Charge Cycling on the Thermal Safety of Lithium-Ion Batteries

Abstract: The safety of the degraded lithium-ion batteries has an essential impact on second life application. This study systematically investigates the thermal safety changes of lithium-ion batteries after deep aging under the fast charge aging path and reveals the degradation mechanisms caused by fast charge cycling. Lithium plating is the primary degradation mechanism, which thickens the solid electrolyte interface film, causes the loss of active lithium and electrolyte, and leads to a significant increase in impeda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…These adverse factors may change the conductivity of the electrolyte and lead to the degradation of lifetime. [14,15] The relationship between degradation mechanism and thermal safety characteristics was showed orderly in Figure 1. [15]…”
Section: Challenges For High-voltage and Fast-charge Electrolytesmentioning
confidence: 99%
See 1 more Smart Citation
“…These adverse factors may change the conductivity of the electrolyte and lead to the degradation of lifetime. [14,15] The relationship between degradation mechanism and thermal safety characteristics was showed orderly in Figure 1. [15]…”
Section: Challenges For High-voltage and Fast-charge Electrolytesmentioning
confidence: 99%
“…[14,15] The relationship between degradation mechanism and thermal safety characteristics was showed orderly in Figure 1. [15]…”
Section: Challenges For High-voltage and Fast-charge Electrolytesmentioning
confidence: 99%
“…In addition, some researchers have also studied the effect of aging on the heat generation characteristics of lithium-ion batteries during charging/discharging. Zhang found that the total heat generation decreased while the heat generation rate increased significantly during the discharge process under the fast charge aging path . Zhang found that electrical abuse, such as overcharge and overdischarge, could significantly increase the heat generation during charging/discharging .…”
Section: Introductionmentioning
confidence: 99%
“…Zhang found that the total heat generation decreased while the heat generation rate increased significantly during the discharge process under the fast charge aging path. 31 Zhang found that electrical abuse, such as overcharge and overdischarge, could significantly increase the heat generation during charging/discharging. 32 Huang found that the larger the charge/discharge rate is, the more the heat generation is.…”
Section: Introductionmentioning
confidence: 99%
“…7−11 However, due to some inherent limitations, they suffer from long-lasting detrimental loss of capacity of the LIBs. 12,13 In this regard, the electrolyte formulation strategy comes into play, where different additives are added to the conventional electrolytes in order to improve the battery performance. 14−18 Commonly, the electrolyte additives usually comprise of functional molecules that are preferentially involved in the interfacial redox process thereby prior to the electrolytes.…”
mentioning
confidence: 99%